If it's not what You are looking for type in the equation solver your own equation and let us solve it.
m in (-oo:+oo)
2*m-(3/4) = -4 // + 4
2*m-(3/4)+4 = 0
2*m-3/4+4 = 0
2*m+13/4 = 0 // - 13/4
2*m = -13/4 // : 2
m = -13/4/2
m = -13/8
m = -13/8
| 3(y+7)-8y=1 | | [5x-6]= | | (2m-3)/4=-4 | | 9x+3=4x+10 | | 2x(x+6x+8)= | | -4d=32 | | 8y+8=24 | | 2b-2=12-b | | 9x+2x=66 | | 8(-6a+12q-5)= | | 93-u=191 | | .5(5-7x)=8-(4+6x) | | 1-3t=-20 | | 1/6i=3 | | (5n+9)= | | 7/15=140c | | 150/97.5=120/g | | 5n^2+90=-45n | | 42-3r=21 | | 3f/7=6 | | x=90+0.2x | | 81y^6/9y^4 | | 3.6d=0.9 | | 7(-5-7n)-5=-3n-40 | | 53=59-m | | 9.4w-2.33=13.2w+19.33 | | 3(72/12)-u=5 | | 4m-3/2=1 | | x+y+z-4= | | (4r-6p)(4r+5p)= | | 6x-4=70 | | 4/6=p/9 |